2011
DOI: 10.1089/vim.2011.0035
|View full text |Cite
|
Sign up to set email alerts
|

CXCR3 Expression Elevated on Peripheral CD8+Lymphocytes from HIV/HCV Coinfected Individuals

Abstract: HIV/HCV coinfected patients tend to develop hepatitis C (HCV)-associated liver disorders. Because the chemokine receptor CXCR3 participates in lymphocyte trafficking during hepatic inflammation, it may participate in the escalated liver disorders of coinfected patients. However, to date, the relative frequency and density of receptor on lymphocytes has not been established. This study compared the CXCR3(+) phenotype under various in vitro conditions between lymphocytes from healthy and coinfected individuals. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
0
5
1
Order By: Relevance
“…hepatocytes, Kupffer cells, hepatic stellate cells) express these chemokines as a response to cellular injury and stress [20][21][22][23][24][25], suggesting a hepatic release of these chemokines. However, it was also implicated that circulating immune cells might contribute to elevated chemokine levels [23,29]. Our data do not support a distinct place of production or clearance of CXCL9.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…hepatocytes, Kupffer cells, hepatic stellate cells) express these chemokines as a response to cellular injury and stress [20][21][22][23][24][25], suggesting a hepatic release of these chemokines. However, it was also implicated that circulating immune cells might contribute to elevated chemokine levels [23,29]. Our data do not support a distinct place of production or clearance of CXCL9.…”
Section: Discussioncontrasting
confidence: 66%
“…The increased intrahepatic levels of CXCR3 ligands during liver disease are also paralleled by elevated serum levels, as demonstrated in various animal and human studies [8,11,13,14,[16][17][18][19][26][27][28]. Circulating inflammatory cells, in addition to liver resident cells, might contribute to their synthesis and secretion as shown previously [23,29].…”
Section: Introductionmentioning
confidence: 81%
“…Chemokine receptor CXCR3 and its ligands (particularly IP-10) are associated with a type 1 response and recruit lymphocytes to the liver [ 39 , 40 ]. Kimball et al [ 41 ] have previously demonstrated an increased CXCR3 expression on CD8 + T cells from HIV-HCV co-infected patients as compared to healthy controls. A recent study showed HCV infection to be associated with significantly increased frequency of CXCR3 + CD56 bright NK cells but these cells showed an impaired degranulation and IFN-γ secretion in response to hepatic stellate cells (HSCs) [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Liver resident cells are supposed to express these chemokines as a response to cellular injury and their activation (25,34,(38)(39)(40)(41). Besides liver resident cells, circulating immune cells also express high levels of these chemokines when activated (34,42). Therefore systemic inflammation might additionally influence levels of CXCL11.…”
Section: Discussionmentioning
confidence: 99%